2020
DOI: 10.1016/j.ijso.2020.05.010
|View full text |Cite
|
Sign up to set email alerts
|

Global prevalence and determinants of preoperative anxiety among surgical patients: A systematic review and meta-analysis

Abstract: Background: Preoperative anxiety, otherwise managed preoperatively, can cause high rate of cardiac mortality, adverse effects during anesthetic induction and patient recovery which correlate with high postoperative pain, increased analgesic and anesthetic consumption, prolonged hospital stay, poor quality of life decrease satisfaction with perioperative care. Objective: The systematic review and meta-analysis aimed to provide evidence on global prevalen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
80
1
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 95 publications
(87 citation statements)
references
References 71 publications
4
80
1
2
Order By: Relevance
“…The pooled estimate in the current review was higher when compared with the pooled prevalence reported in a global level systematic review and meta-analysis that included 14 652 study participants (48%). 7 Likewise, the pooled estimate of our review was higher than the estimates from different epidemiological studies conducted in HICs such as the Netherlands reported that 27.9% and 20.3% of patients undergoing hip and knee surgery, respectively, experienced anxiety symptoms before the actual surgery. 8 The variation in the demographic characteristics of participants and may partly explain the observed difference in the pooled estimates.…”
Section: Discussioncontrasting
confidence: 68%
See 1 more Smart Citation
“…The pooled estimate in the current review was higher when compared with the pooled prevalence reported in a global level systematic review and meta-analysis that included 14 652 study participants (48%). 7 Likewise, the pooled estimate of our review was higher than the estimates from different epidemiological studies conducted in HICs such as the Netherlands reported that 27.9% and 20.3% of patients undergoing hip and knee surgery, respectively, experienced anxiety symptoms before the actual surgery. 8 The variation in the demographic characteristics of participants and may partly explain the observed difference in the pooled estimates.…”
Section: Discussioncontrasting
confidence: 68%
“…For example, a global level systematic review and meta-analysis reported a 48% pooled prevalence of preoperative anxiety among patients undergoing surgery. 7 A facility-based study conducted in Netherland found 27.9% and 20.3% of preoperative anxiety in patients undergoing hip and knee surgery, respectively. 8 Epidemiological studies conducted in low/middle-income countries (LMICs) found that the prevalence of preoperative…”
Section: Introductionmentioning
confidence: 99%
“…A 2020 study found that 48% of surgical patients are anxious before their surgery [5]. This anxiety will have an impact on both the flow of the surgery and the post-operative recovery process [6][7][8].…”
Section: Introductionmentioning
confidence: 99%
“…Preoperative anxiety, feelings of discomfort and tension, along with other physical and autonomic symptoms, therefore results before surgery [ 3 , 4 ]. A 2020 study found that 48% of surgical patients are anxious before their surgery [ 5 ]. This anxiety will have an impact on both the flow of the surgery and the post-operative recovery process [ 6 , 7 , 8 ].…”
Section: Introductionmentioning
confidence: 99%
“…9,13 Globally, approximately 50% of patients scheduled for elective surgery experienced preoperative anxiety. 14 Studies reported from different countries showed that the prevalence of preoperative anxiety was high. Besides, the prevalence of preoperative anxiety was 53% in Brazil, 15 63% in Pakistan, 16 67% in Tunisia, 17 and 72.8% in Rwanda.…”
mentioning
confidence: 99%